BIOLOGIC DIVERSITY OF POLYOMAVIRUS BK GENOMIC SEQUENCES: IMPLICATIONS FOR MOLECULAR DIAGNOSTIC LABORATORIES - Luo, C (2008)
Data on polyomavirus genomic diversity has greatly expanded in the past few years. The implications of viral DNA sequence variation on the performance of molecular diagnostic assays have not been systematically examined. 716 BK, 1626 JC and 73 SV40 virus sequences available in GenBank were aligned using Clustal-X. Five different published BKV PCR assays currently in use at major medical centers were evaluated for primer and probe mismatches with available GenBank sequences. Coverage of naturally occurring BKV strains varied amongst different assay methods. Targeted viral sequences showed major mismatch with primer or probe sequence in up to 30.7% of known BKV strains. BKV subtypes IVa, IVb, and IVc were more prone to this problem, reflecting common use of Type I Dun sequence for assay design. Despite the known polymorphism of this gene, 484 VP-1 sequences with conserved areas potentially suitable for PCR assay design are available. Assay targets in the Large T-antigen and agnogene are less subject to genetic variation, but sequence information corresponding to the latter two genes is available only for 164 and 174 published strains respectively. Cross reactivity of appropriately selected BKV primers with JCV and SV40 sequences available in current databases was not a significant problem.